open import Cat.Prelude open import Cat.Displayed.Base open import Cat.Displayed.Functor open import Cat.Displayed.Total open import Cat.Displayed.Cartesian import Cat.Displayed.Reasoning as DR module Cat.Displayed.Composition where

# Composition of Displayed Categories🔗

A displayed category $\mathcal{E}$ over $\mathcal{B}$ is equivalent to the data of a functor into $\mathcal{B}$; the forward direction of this equivalence is witnessed by the [total category] of $\mathcal{E}$, along with the canonical projection functor from the total category into $\mathcal{B}$. This suggests that we ought to be able to compose displayed categories. That is, if $\mathcal{E}$ is displayed over $\mathcal{B}$, and $\mathcal{F}$ is displayed over $\int \mathcal{E}$, then we can construct a new category $\mathcal{E} \cdot \mathcal{F}$ displayed over $\mathcal{B}$ that contains the data of both $\mathcal{E}$ and $\mathcal{F}$.

[total category] Cat.Displayed.Total.html

To actually construct the composite, we bundle up the data of $\mathcal{E}$ and $\mathcal{F}$ into pairs, so an object in $\mathcal{E} \cdot \mathcal{F}$ over $X : \mathcal{B}$ consists of a pair objects of $X' : \mathcal{E}$ over $X$, and $X'' : \mathcal{F}$ over $X$ and $X'$. Morphisms are defined similarly, as do equations.

_D∘_ : ∀ {o ℓ o′ ℓ′ o″ ℓ″} → {ℬ : Precategory o ℓ} → (ℰ : Displayed ℬ o′ ℓ′) → (ℱ : Displayed (∫ ℰ) o″ ℓ″) → Displayed ℬ (o′ ⊔ o″) (ℓ′ ⊔ ℓ″) _D∘_ {ℬ = ℬ} ℰ ℱ = disp where module ℰ = Displayed ℰ module ℱ = Displayed ℱ disp : Displayed ℬ _ _ Displayed.Ob[ disp ] X = Σ[ X′ ∈ ℰ.Ob[ X ] ] ℱ.Ob[ X , X′ ] Displayed.Hom[ disp ] f X Y = Σ[ f′ ∈ ℰ.Hom[ f ] (X .fst) (Y .fst) ] ℱ.Hom[ total-hom f f′ ] (X .snd) (Y .snd) Displayed.Hom[ disp ]-set f x y = Σ-is-hlevel 2 (ℰ.Hom[ f ]-set (x .fst) (y .fst)) λ f′ → ℱ.Hom[ total-hom f f′ ]-set (x .snd) (y .snd) disp .Displayed.id′ = ℰ.id′ , ℱ.id′ disp .Displayed._∘′_ f′ g′ = (f′ .fst ℰ.∘′ g′ .fst) , (f′ .snd ℱ.∘′ g′ .snd) disp .Displayed.idr′ f′ = ℰ.idr′ (f′ .fst) ,ₚ ℱ.idr′ (f′ .snd) disp .Displayed.idl′ f′ = ℰ.idl′ (f′ .fst) ,ₚ ℱ.idl′ (f′ .snd) disp .Displayed.assoc′ f′ g′ h′ = (ℰ.assoc′ (f′ .fst) (g′ .fst) (h′ .fst)) ,ₚ (ℱ.assoc′ (f′ .snd) (g′ .snd) (h′ .snd))

We also obtain a displayed functor from $\mathcal{E} \cdot \mathcal{F}$ to $\mathcal{E}$ that projects out the data of $\mathcal{E}$ from the composite.

πᵈ : ∀ {o ℓ o′ ℓ′ o″ ℓ″} → {ℬ : Precategory o ℓ} → {ℰ : Displayed ℬ o′ ℓ′} {ℱ : Displayed (∫ ℰ) o″ ℓ″} → Displayed-functor (ℰ D∘ ℱ) ℰ Id πᵈ .Displayed-functor.F₀′ = fst πᵈ .Displayed-functor.F₁′ = fst πᵈ .Displayed-functor.F-id′ = refl πᵈ .Displayed-functor.F-∘′ = refl

## Composition of fibrations🔗

As one may expect, the composition of fibrations is itself a fibration.

The idea of the proof is that we can take lifts of lifts, and in fact, this is exactly how we construct the liftings.

fibration-∘ : Cartesian-fibration ℰ → Cartesian-fibration ℱ → Cartesian-fibration (ℰ D∘ ℱ) fibration-∘ ℰ-fib ℱ-fib = ℰ∘ℱ-fib where open Cartesian-fibration open Cartesian-lift ℰ∘ℱ-fib : Cartesian-fibration (ℰ D∘ ℱ) ℰ∘ℱ-fib .has-lift f (y′ , y″) = cart-lift where ℰ-lift = ℰ-fib .has-lift f y′ ℱ-lift = ℱ-fib .has-lift (total-hom f (ℰ-lift .lifting)) y″ cart-lift : Cartesian-lift (ℰ D∘ ℱ) f (y′ , y″) cart-lift .x′ = ℰ-lift .x′ , ℱ-lift .x′ cart-lift .lifting = ℰ-lift .lifting , ℱ-lift .lifting

However, showing that the constructed lift is cartesian is somewhat
more subtle. The issue is that when we go to construct the universal
map, we are handed an
$h'$
displayed over
$f \cdot m$,
and also an
$h''$
displayed over
$f \cdot m, h'$,
which is not a composite definitionally. However, it is
*propositionally* a composite, as is witnessed by
`ℰ-lift .commutes`

, so we can use the generalized
propositional functions of `ℱ-lift`

to construct the
universal map, and show that it is indeed universal.

cart-lift .cartesian .is-cartesian.universal m (h′ , h″) = ℰ-lift .universal m h′ , universal′ ℱ-lift (total-hom-path ℰ refl (ℰ-lift .commutes m h′)) h″ cart-lift .cartesian .is-cartesian.commutes m h′ = ℰ-lift .commutes m (h′ .fst) ,ₚ commutesp ℱ-lift _ (h′ .snd) cart-lift .cartesian .is-cartesian.unique m′ p = ℰ-lift .unique (m′ .fst) (ap fst p) ,ₚ uniquep ℱ-lift _ _ (total-hom-path ℰ refl (ℰ-lift .commutes _ _)) (m′ .snd) (ap snd p)